Synthesis and properties of a novel UV/moisture dual-curable polyurethane resin derived from vinyl-based polyether polyol. Issue 8 (18th April 2021) - Zong, Hongliang; Fang, Cheng; Lin, Zhongxiang; Yan, Qiming; Lin, Xing
Abstract: A novel UV/moisture dual-curable polyurethane resin has been synthesized via a two-step process. In the first step, methoxysilane-modified polyether polyol (SPOL) was prepared through the thiolene click reaction between sulfhydryl group in (3-mercaptopropyl)trimethoxysilane (KH590) and vinyl groups in polyether polyol. In the second step, the obtained SPOL was reacted with hydroxyethyl methacrylate (HEMA)/pentaerythritol triacrylate (PETA) and isophorone diisocyanate (IPDI) to form UV/moisture dual-curable polyurethane adhesive (DPUA). The vinyl-based polyether polyol was obtained from 4-vinyl-1-cyclohexene-1, 2-epoxide (VCHO), propylene oxide (PO) and poly(propylene glycol) (PPG 400) through ring-opening polymerization. Strikingly, the properties of the DPUA can be easily controlled by changing the type of blocking agents and the content of KH590. The DPUA film using PETA as a blocking agent possesses higher mechanical strength, storage modulus ( E ′, glass transition temperature ( T g ) and better thermal properties than that with HEMA as a blocking agent due to the higher crosslink density. Besides, similar trends can be observed by increasing the content of KH590 or decreasing the molecular weight of vinyl-based polyether polyol. In addition, using PETA as a blocking agent or decreasing the molecular weight of vinyl-based polyether polyol, the tensile strength increases while the elongation at break decreases. Especially, the tensile strength and the elongation at break can be increased by increasing the content of KH590.